Analisis Penerapan Metode Scrum Pada Sistem Informasi Manajemen Proyek Dalam Industri & Organisasi Digital - Suharno, Hisyam Rahmawan; Gunantara, Nyoman; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2020)
The rapid evolution of information technology in this era requires appropriate adjustments in utilizing information technology. All fields of life require some forms of information technology, particularly digital organizations and digital industries that are heavily reliant on information system. In order to create an information system, a software development method is needed. There are various types of software development methods, one of which is often used is the SDCL Waterfall method. SDCL Waterfall in principle follows organized and systematic stages. The Waterfall method emphasizes clearly the requirements for a software that will be developed. Therefore, some problems when a software will be developed like the initial requirements are not so clear and the possibility for changes during development. In line with the evolution of technology, the software development method has also evolved. There is a new method known as the scrum method. The scrum method is allegedly faster and more efficient. This translates to a more flexible implementation as this method prioritizes fast iteration or delivery based on functionality of the software that will be developed. However, not all software development is compatible with the scrum method. Thereforethis research will conduct a literature study to observe the effectiveness of applying the scrum method to digital industries & organizations, and to find out whether the scrum method is truly reliable as a software development work scheme in an industry or digital organization.